Menstrual problems of school going unmarried adolescent girls and their treatment seeking behavior in Chandigarh, India - Kumar, Dinesh; Goel, Naveen K.; Sharma, Munesh K.; Kaur, Gurleen (International Journal Of Community Medicine And Public Health, 2016)
Background: Menstruation is a vital part of the reproductive health of a woman. There is evident neglect of problems related to menstruation especially in young girls. Lack of awareness and non-availability of adolescent friendly health facilities and other factors hinder the treatment seeking behavior of adolescent girls. The objectives were to assess the prevalence and patterns of menstrual problems among school-going adolescent girls and to investigate their treatment seeking behavior for menstrual problems. Methods: Present study is based on part of a detailed survey under ICMR sponsored project. A stratified multistage sampling design was adopted for selection of participants from the 12 of Chandigarh. A total of 655 girls who had attained menarche were selected. Information on background and menstrual characteristics was collected through personal interviews conducted in privacy using semi -structured survey schedule. Results: About 36% of 655 surveyed girls attained menarche prior to age of 13 years. Prior knowledge regarding menses was reported by 80% girls and mother was the main source of information. Overall prevalence of menstrual problem in the present study was found 64.6%. Abdominal pain was the most common menstrual problem reported by 62.6% of participants having menstrual problems. Excessive menstrual flow was reported by 10.4% girls. Pre-menstrual problems were reported by 57.4% participants. Treatment seeking behaviour of the girls was poor and only about 25% of girls having menstrual problems approached for treatment. Reliance on home remedies followed by shyness / hesitation came out to be the major reasons of not approaching for treatment in the present study. Use of painkiller in the present study was found to be 34.8%. Conclusions: Study concludes that menstrual problems among girls are highly prevalent. Adolescent girls should be offered possible treatment options with adolescent friendly approach. Reproductive health education in the school curriculum should be introduced for improving awareness regarding menstrual care practices. Mentorship program in the school set-up may result in desired improvements providing adolescent friendly health services for sharing their menstrual and other problems.